INVENTORY TURNOVER AND INVENTORY MARKDOWNS. (The Accounting Review, 1933)
Abstract This article presents information on the methods of calculating inventory turnover and the inventory markdowns. In calculating turnover by the cost method, it is essential that numerator and denominator should be on the same price level otherwise a distortion would result. The prevailing practice of taking inventory at cost or market and deducting this inventory from purchases at cost, cause an error that gives a Cost of Goods Sold figure containing part of the cost of goods unsold and also results in a double distortion of the turnover. The ratio of sales to net worth or "turnover of owned capital" is sometimes suggested as a test of the efficiency with which the investor's dollar is being used. Since efficiency of utilization of assets is a factor quite independent of the borrowing policy, the two can be measured separately, the borrowing policy by the ratio of net worth to debt and the efficiency of asset utilization by the ratio of sales to total assets.